2014
DOI: 10.7727/wimj.2013.113
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Leukopenia and Intercellular Adhesion Molecules in Graves’ Disease

Abstract: Objective: Changes in soluble intercellular adhesion molecule-1 (sICAM-1) and E-selectin levels as well as leukocyte count were examined in this study to explore the relationship between leukopenia and ICAMs in Graves' disease (GD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Only one study 11 reported that morning ANCs were repeated in several instances. Preexisting diseases (ie infections, cancer, haematological or rheumatological disorders) or the use of drugs (including iron and methotrexate) potentially influencing the development of neutropenia were reported in some studies 10,12,13,18,20‐24 as exclusion criteria of hyperthyroid patients. Smoking habits were explored in only two studies 10,13 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one study 11 reported that morning ANCs were repeated in several instances. Preexisting diseases (ie infections, cancer, haematological or rheumatological disorders) or the use of drugs (including iron and methotrexate) potentially influencing the development of neutropenia were reported in some studies 10,12,13,18,20‐24 as exclusion criteria of hyperthyroid patients. Smoking habits were explored in only two studies 10,13 .…”
Section: Resultsmentioning
confidence: 99%
“…Neutropenia (ANC < 1.8 × 10 9 /L) was found in 103 cases who were all affected by hyperthyroidism due to Graves’ disease. In the study by Gao et al, 24 the cut‐off to define neutropenia was 1.5x10 9 /L.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graves disease is often associated with leukopenia, mainly agranulocytosis and the speci c mechanisms thought to be involved includes marrow depression, anti-neutrophil antibodies etc. [28] It has been suggested that a cross antigenicity between TSH receptors and polynuclear neutrophils, a decreased circulating time of granulocytes and reduced marrow granulocyte reserve are the causes of neutropenia in thyrotoxicosis. [29,30] However, these still remain controversial .When slight leucopenia, neutropenia and thrombocytopenia are common manifestations of Graves disease even in untreated cases and believed to be an autoimmune process, use of anti-thyroid medications mainly Thiamazole could cause serious life-threatening agranulocytosis.…”
Section: Discussionmentioning
confidence: 99%